Linking key antecedents of hotel information management system adoption to innovative work behavior through attitudinal engagement - Omuudu, Otengei Samson; Francis, Kasekende; Changha, George (Journal of Hospitality and Tourism Insights, 2021)
The paper aims to examine the relationship between the key antecedents of hotel information management system (HIMS) adoption and innovative work behavior (IWB) with attitudinal engagement as a mediator. Design/methodology/approach – Survey data were obtained from 297 full-time employees in five-star hotels in Uganda. With the help of Analysis of Moment Structures (AMOS), seven hypotheses were tested and analyzed using structural equation modeling (SEM). Findings – Both perceived usefulness and perceived ease of use are significant determinants of IWB. The study also confirms attitudinal engagement as a significant predictor of IWB. Importantly, attitudinal engagement was found to be a partial mediator in both the perceived usefulness and the perceived ease–IWB relationships. Practical implications – The study’s findings will guide managers in formulating policies that promote employee display of vigor, absorption and dedication to work. Hospitality and tourism firms can now keep their workers abreast with the latest technology at work so as to help them exhibit engagement tendencies as well as generating new ideas for the organization. Originality/value – The proposed framework provides a fresh theoretical explanation for IWB in hotels with perceived technology beliefs and attitudinal engagement as major drivers, hence contributing to the current state of knowledge. The study demonstrates that engagement acts as a link for the transfer of part of the contributions of both perceived usefulness (PUHIMS) and perceived ease of use of HIMS (PEUHIMS) into IWB.
Keywords: Innovative work behavior; Attitudinal engagement; Perceived usefulness; Perceived ease of use; Hotel information management system